Evaluasi Pertumbuhan Sambungan Eucalyptus Pellita F. Muell Dengan Teknik Veneer Grafting - Adma Adinugraha, Hamdan; Ranti Fani, Trisya; Hadiyan, Yayan (Jurnal Sylva Lestari, 2016)
Eucalyptus pellita F. Muell is one of the promising species for pulp production in Indonesia. Tree breeding activities of this species have been developed to investigate a high productivity of Eucalypt through the selection of genetically improved individual trees. Vegetative propagation technique is an important tool needed to multiple the trees. Veneer Grafting is one of the recommended propagation techniques. The objective of the research is to study the compatibility of several E. Pellita clones that are produced from plus trees. Implemented by Completely Randomized Design (CRD), the research was used 36 E. pellita families and 6 hibryds of E. pellita x E. brassiana as the treatment with 4 replications. The result showed that the clone of E. pellita was significantly different effecting growth variation of clone adaptability, shoot number, shoot length, and shoot diameter. Clone adaptability was range from 0 - 100%. Shoot number was around 1-3 stems. Shoot length was range 0.17 cm - 17.82 cm and the shoot diameter was 0.10 mm - 2.27 mm in range. The clone (number 19) from Keru To Nata WP Papua New Guinea was invented as the best in adaptability (100%) during the observation period, while clone (number 33) was the best growth performance in shoot number, shoot diameter and shoot length. Keywords: Growth, Eucalyptus pellita, veneer grafting